Associations of Nutritional, Lifestyle, and Metabolic Factors With Non-alcoholic Fatty Liver Disease: An Umbrella Review With More Than 380,000 Participants - Xia, Yang; Wu, Qijun; Dai, Huixu; Lv, Jiale; Liu, Yashu; Sun, Hui; Jiang, Yuting; Chang, Qing; Niu, Kaijun; Zhao, Yuhong (Frontiers in Nutrition, 2021)
Background & Aims: Nonalcoholic fatty liver disease (NAFLD) is the most common liver injury. We performed this umbrella review of meta-analyses to summarize the evidence on the associations of nutritional, lifestyle, and metabolic factors with NAFLD. Methods: We searched the PubMed, Embase, and Web of Science databases from inception until July 2, 2020, to identify meta-analyses of observational studies which explored the associations of nutritional, lifestyle, and metabolic factors with NAFLD. Evidence levels were assessed using summary effect sizes, 95% prediction intervals, between-study heterogeneity, evidence of small-study effects, and evidence of excess significance bias for each meta-analysis. (No. of PROSPERO, CRD42020200124). Results: Twenty two risk or protective factors from 10 published meta-analyses were included and studied. Three risk factors (sugar-sweetened beverage consumption, serum fetuin-A, and waist circumference) with highly suggestive levels of evidence and three risk factors (soft drink consumption, former smoking, and body mass index) with suggestive levels of evidence were identified. Only two protective factors (physical activity and serum vitamin D level [among adults in Western countries]) with suggestive levels of evidence were identified. Furthermore, other six risk factors and two protective factors with weak levels of evidence were identified. Conclusions: We found varying levels of evidence of associations of nutritional, lifestyle, and metabolic factors and NAFLD. The results suggest that nutritional and lifestyle management should be considered as a major primary preventive strategy for NAFLD. Moreover, considering the low quality of included meta-analyses and limited area of research topics, future high-quality original studies and meta-analyses should be performed to study these associations.